बीजगणितीय सूत्र

बीजगणितीय सूत्र
आधारभूत सूत्र

(a+b)²=a²+b²+2ab

(a-b)²=a²+b²-2ab
a²+b²=(a+b)²-2ab
a²+b²=(a-b)²+2ab
(a+b)²-(a-b)²=4ab
(a+b)²+(a-b)²=2(a²+b²)
a²-b²=(a+b)(a-b)
(a+b)³=a³+b³+3a²b+3ab²
(a+b)³=a³+b³+3ab(a+b)
(a-b)³=a³-b³-3a²b+3ab²
(a-b)³=a³-b³-3ab(a-b)
a³+b³=(a+b)(a²-ab+b²)
a³+b³=(a+b)³-3ab(a+b)
a³-b³=(a-b)(a²+ab+b²)
a³-b³=(a-b)³+3ab(a-b)
यदि a+b+c=0,तो a³+b³+c³=3abc

घातांक एवम् करणी से सम्बंधित सूत्र
[begin{align} & {{a}^{m}}times {{a}^{n}}={{a}^{m+n}} \ & frac{{{a}^{m}}}{{{a}^{n}}}={{a}^{m-n}} \ & {{({{a}^{m}})}^{n}}={{a}^{mn}} \ end{align}]

[{(ab)^m} = {a^m} times {b^m}]

Updated: June 18, 2020 — 10:37 am

Leave a Reply

Your email address will not be published. Required fields are marked *